Grammatical Cohesive Devices in Reading Text: A Discourse Analysis of English Test for Junior High School - Jayanti, Dwi; Hidayat, Didin Nuruddin (JET ADI BUANA, 2021)
Reading text, besides being used as teaching media, is also used in an assessment measurement. However, in reality, many students have difficulty understanding the reading text due to several factors such as the text is too long, incohesive between words, and even incoherent between paragraphs. To avoid these factors, important to analyze the use of cohesive devices in reading texts. The present study aimed to investigate grammatical cohesive devices in the reading text of the English National Final Examination test for Junior High School in the 2017-2018 academic year in Indonesia. The current research attempted to: (1) find out the kind of grammatical cohesion devices that were applied in sixteen reading texts of the English National Final Examination test, (2) explore the use of reference, substitution, ellipses, and conjunction to describe the cohesiveness that was applied in sixteen of the reading texts, consisting of a short functional, narrative, descriptive, recount and report text. The reading texts were analyzed using Halliday and Hasan’s (1976) theory related to grammatical cohesion devices. The steps of data analysis were through the process of collecting, counting, categorizing, and assessing the grammatical cohesion devices. The findings revealed that 621 grammatical cohesion devices were used in the English National Final Examination reading text. Further, the findings explained that 67.47% of grammatical cohesion device was the reference (419), 5.15% was the substitution (32), 2.58% was the ellipses (16), 24.80% was the conjunction (154). The findings also indicated that the limited use of grammatical cohesion devices in the present study showed a lack of a variety of grammatical cohesion in terms of form and variation devices. Although the reading text of the English Final Examination was somewhat cohesive, some areas still need improvement. Implications for teachers and educators are to give more attention to the coherence of the reading text. A cohesive reading text will provide an understanding of both the form and content of the text. For reading text scriptwriters, they must pay attention to grammatical cohesion devices so it becomes more varied and not monotonous. Besides, students need to be given material related to cohesion because knowledge of cohesion is very useful in the mastery of their language, especially in reading and writing skills.